A novel integrated biorefinery approach for apple pomace valorization with significant socioeconomic benefits. (May 2023) - Borujeni, Nasim Espah; Alavijeh, Masih Karimi; Denayer, Joeri F.M.; Karimi, Keikhosro
Abstract: Ethanolic organosolv pretreatment was used to enhance the yield of ethanol production from apple pomace through a biorefinery. The pretreatment was conducted at various conditions (100, 150, and 180 °C; 30 and 60 min; 50 and 85% ethanol) in the absence or presence of 0.5% sulfuric acid. Then, pectin was extracted from the pretreatment liquor, the solvent (i.e., ethanol) was recovered by distillation, lignin was separated, and the pretreated solid was subjected to simultaneous saccharification and fermentation for ethanol production. The highest ethanol yield was achieved when the pretreatment was performed at 100 °C for 30 min with 50% ethanol in the absence of sulfuric acid, giving an overall yield of 173.3 g ethanol per 1 kg of untreated pomace. Besides, under these conditions, the amounts of extracted pectin and lignin were 76 g and 3 g per each kg of the untreated pomace, respectively. The study of socioeconomic impacts of the optimized biorefinery indicated that a total of 59.3 million liters of ethanol could potentially be generated from collectible apple pomace in Iran per annum, leading to a significant reduction in well-to-wheel greenhouse gas emissions of 84.9 and 85.6 (kt CO2 equivalent) using apple-pomace-ethanol-blended fuels of E85 and E10, respectively. Graphical abstract: Image 1